2020
DOI: 10.1016/j.compbiomed.2020.103869
|View full text |Cite
|
Sign up to set email alerts
|

CovXNet: A multi-dilation convolutional neural network for automatic COVID-19 and other pneumonia detection from chest X-ray images with transferable multi-receptive feature optimization

Abstract: With the recent outbreak of COVID-19, fast diagnostic testing has become one of the major challenges due to the critical shortage of test kit. Pneumonia, a major effect of COVID-19, needs to be urgently diagnosed along with its underlying reasons. In this paper, deep learning aided automated COVID-19 and other pneumonia detection schemes are proposed utilizing a small amount of COVID-19 chest X-rays. A deep convolutional neural network (CNN) based architecture, named as CovXNet, is proposed that utilizes depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
362
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(370 citation statements)
references
References 23 publications
1
362
0
7
Order By: Relevance
“…With regards to the classi cation of COVID-19 and normal CXR images, it can be observed that our model provides signi cantly a better performance compare to studies that utilized small amount of dataset such as Mahmud et al, 2020 [34] and models developed from scratch. The impressive performance of the model is attributed to the use of TL based on pretrained models which have shown to perform e ciently with less amount of data compare to models designed from scratch such as Tan et al, 2018 [19].…”
Section: Comparison Between Our Results With State Of Artmentioning
confidence: 70%
See 1 more Smart Citation
“…With regards to the classi cation of COVID-19 and normal CXR images, it can be observed that our model provides signi cantly a better performance compare to studies that utilized small amount of dataset such as Mahmud et al, 2020 [34] and models developed from scratch. The impressive performance of the model is attributed to the use of TL based on pretrained models which have shown to perform e ciently with less amount of data compare to models designed from scratch such as Tan et al, 2018 [19].…”
Section: Comparison Between Our Results With State Of Artmentioning
confidence: 70%
“…The models achieved higher accuracies, sensitivities and speci cities. A multi dilation CNN is utilized by Mahmud et al, 2020[34] to classify COVID-19 and other forms of pneumonia. The study utilized a deep CNN as COVXNet with modi cations base on varying dilation rates for feature extraction, optimization, stacking algorithms and gradient-based discriminative localization to train dataset containing 1493 Non-COVID-19 viral pneumonia, 305 COVID-19 pneumonia, 2780 bacterial pneumonia.…”
mentioning
confidence: 99%
“…On the contrary, some papers apparently stated the size of the train-test-validation data of COVID-19 images [16], [20], [22] and for those papers, I computed the ratio according to the split that was provided. Even so, for some papers, the distribution of the dataset [7], [10], [26] was not clearly mentioned. Moreover, some papers apparently mentioned the use of data for validation [1], [16], [25], [30] along with some papers do not state exact data instead provide a comparison based on 10-fold cross-validation [6], 5-fold cross-validation [3,[18] for performance assessment.…”
Section: Experimental Results For X-ray Imagesmentioning
confidence: 99%
“…Moreover, some researchers also use an adaptive winner filter for noise reduction [59], Affine Transformation [31] in their research. [2], [5], [6], [8], [10][11], [16], [18], [19], [20], [22], [23] [24],[ [26], [28], [ 30], [32], [37],43], [45], [46], [48], [50], [53], [54], [56], [60], [61], [63], [67] 31…”
Section: Generative Adversarial Network(gan)mentioning
confidence: 99%
See 1 more Smart Citation